Long Term Post-Treatment Follow-Up of Pituitary Tumours - Paras Imran, Tasnim Ahsan, Heer Dilawar, Saeeda Fouzia Qasim, Bharta Rani, Wasfa Aijaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To study the spectrum of Pituitary tumours, their presentation, treatment and compliance with follow-up. Study design: Mixed retrospective and prospective study Place and duration of study: Medicell Institute of Diabetes, Endocrinology and Metabolism and Jinnah Postgraduate Medical Centre Karachi from 1st January 2012 to 31st July 2022. Methodology: One hundred and seventy three cases of pituitary tumours, were enrolled. Data regarding age, gender, duration of disease, symptoms, mode of treatment administered and compliance with the follow-up instructions was retrieved. Results: The mean age was 36.4±10.6 years. Female predominance was seen in 97(56.1%). Of the 136 married patients, subfertility was seen in 48(36.3%). Headache was observed in 164(94.8%) of patients. Prolactinoma was the lead tumour comprising of 76 cases (43.9%), followed by non-secretory tumours 47(27.2%), and acromegaly 43(24.9%). Other rare disorders including Cushing’s disease, craniopharyngioma and gonadotropinoma were also seen. Cabergoline was prescribed in 136 (78.6%) cases. Transsphenoidal surgery (TSS) was done in 74(42.8%) of patients. Out of 97 female patients, 38(39.2%) had persistent amenorrhea post-treatment, while this data was not available for 40(41.2%) of these women, who were lost to follow-up. The difference between mean prolactin levels prior and after the treatment (1390.048±2646.986 versus 116.360±163.369) were found to be statistically significant p<0.001). Similarly, IGF-1 levels were significantly improved post treatment indicating tumour stability. Moreover, the level of mean FT4 post-treatment was 1.64, reflecting adequate replacement. Conclusion: Majority of the patients had improvement post-treatment in pituitary tumour symptoms including vision, headache and sexual function. Failure to attend for follow-up for tumour stability, control of excess hormone, and pituitary hormone replacement was seen in a large number of patients in this study. This requires careful consideration of different strategies to ensure better long term care in pituitary tumours. Keywords: Pituitary tumor, Prolactinoma, Craniopharyngioma, Gonadotropinoma, Acromegaly